Professional and Personal Experiences as Leverage for Learning - Kappert, Annette (Frontiers in Education, 2020)
The current transnational climate in Europe is likely to continue to generate institutional and classroom situations which dictate that difference and otherness be the norm rather than the exception. Unfortunately, in the 1960s, Black and minority ethnic (BME) migrants from the former British colonies had less-than-favourable educational experiences in Britain due to prejudice and stereotyping mainly arising from cultural differences. Since then there have been a plethora of studies, policies, and reports regarding the perpetuation of discrimination in educational institutions. Today, British higher educational institutions have finally begun to recognise the need to reduce progression and attainment gaps. However, their focus tends to only consider the student ‘Black and Minority Ethnic attainment gap’ with almost no attention being given to educators’, or more specifically there is a distinctive lack of thought given to the female BME educators’ progression and attainment in British HEIs. As such, this paper draws theoretically and conceptually on critical cultural autoethnography, to illustrate the value of conducting research into a female’s BME educators’ personal and professional experiences, and ‘gives voice to previously silenced and marginalized experiences’ (Boylorn & Orbe, 2014:15). In doing so, I highlight how higher educational institutions underutilisation of such competencies and contributions have and continue to perpetuate BME underachievement. I conclude the paper by questioning the accountability of providing support for BME educators progression and attainment, challenge educational leaders to consider the value and utilization of cultural knowledge, and implore all educators to reflect on how their personal experiences influence their professional identity.